Evaluating Active Learning: The Role of Non-Presential Workload Monitoring in Academic Achievement and Student Satisfaction in Architecture Programs Within the European Higher Education Area - César Daniel Sirvent-Pérez; Carlos Pérez-Carramiñana; Pascual Saura-Gómez; Ángel Benigno González-Avilés; José Ángel Ruiz-Cáceres (Education Sciences, 2025)
The European Higher Education Area (EHEA) university learning framework, structured around the European Credit Transfer and Accumulation System (ECTS), integrates classroom hours with independent, non-classroom workloads outside the university, where students engage in self-directed learning. This study aimed to develop a standardized protocol to monitor and quantify non-presential study hours to identify and adjust anomalous workload values. Over a two-year period, data were gathered from two distinct student groups (local Spanish students and international exchange students) enrolled in the same fourth-year architecture course at the University of Alicante. The data analysis allowed for an exploration of correlations among three key variables: non-presential study hours, final grades, and student satisfaction (self-assessed course perceptions). The results reveal a direct proportional relationship among these variables, whereby an increase in weekly study hours corresponds with both higher final grades and improved student satisfaction with the course.